Assessment of prebiotic potential of Akpan-yoghurt-like product and effects on the human intestinal microbiota. (December 2015) - Gullón, Beatriz; Pereira, Miguel; Mestres, Christian; Hounhouigan, Joseph; Pallet, Dominique; Alonso, José Luis; Pintado, Manuela
Highlights: The effect of Akpan consumption on the human gut microbiota was assessed by in vitro fermentation. Akpan promoted favourable changes in the composition of intestinal microbiota. Moreover, Akpan stimulated the growth of the Bifidobacterium animalis Bb12 and Bifidobacterium lactis B94. The production of metabolic end products also proved the prebiotic potential of Akpan. The production of short-chain fatty acids by fermentation of Akpan was similar to commercial FOS. Abstract: The effect of Akpan (yoghurt-like product) consumption on the human intestinal microbiota was examined. The prebiotic potential of Akpan was assessed by in vitro fermentation using, as inocula, individual probiotic strains and faecal samples from three healthy donors. In this latter case, the prebiotic activity was assessed through the quantification of short chain fatty acid (SCFA) production, the evolution of the pH and the evaluation of dynamic bacterial population by fluorescent in situ hybridization (FISH). Results demonstrated that Akpan was metabolized after 44 h of fermentation, exerting a prebiotic effect, similar to that observed for fructooligosaccharides (FOS). All the considered bacterial groups significantly increased after Akpan and FOS fermentation. Under the tested conditions, no significant differences between the SCFA concentration produced by Akpan and FOS after of incubation were detected. Our findings contribute to support the utilization of Akpan as a functional food with potential beneficial effects on gastrointestinal health.